2017
DOI: 10.1007/s00248-017-1018-7
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont Spillover from Invasive to Native Woodwasps

Abstract: Hosts and their associated microbes are being increasingly introduced around the world, which can lead to novel host/microbe associations via new sympatries. Woodwasps (Hymenoptera: Siricidae) are able to utilize wood for its nutrients due to obligate mutualistic associations with white rot fungi in the genus Amylostereum and when invasive woodwasps are introduced to new areas, their symbionts accompany them. There is increasing evidence that woodwasp-fungus associations previously believed to be highly specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The invasive woodwasp, U . albicornis, has a symbiotic relationship with the fungi Amylostereum areolatum and A. chailletii (Castrillo et al, ; Hajek et al, ), while the native woodwasp U. antennatus is associated with A . laevigatum (Tabata & Abe, ; Tabata et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The invasive woodwasp, U . albicornis, has a symbiotic relationship with the fungi Amylostereum areolatum and A. chailletii (Castrillo et al, ; Hajek et al, ), while the native woodwasp U. antennatus is associated with A . laevigatum (Tabata & Abe, ; Tabata et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…laevigatum (Tabata & Abe, ; Tabata et al, ). Hajek et al () demonstrated symbiont spillover from an invasive woodwasp Sirex noctilio to native woodwasp Urocerus spp. in North America, presumably via horizontal transmission during sequential use of the same wood for larval development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preference for this fungal strain by S. nigricornis in the present study is consistent with the fact that larvae of this native Sirex are known to develop in the same trees as S. noctilio (Long et al ., ; Ryan et al ., ; Hajek et al ., ) and horizontal transmission of Amylostereum between Sirex species appears to occur within trees (Hajek et al ., ; Wooding et al ., ). Sirex species were previously considered specific to single Amylostereum species (Talbot, ; Gilbertson, ), although studies of Sirex and Urocerus have demonstrated flexibility in the Amylostereum species being carried (Wooding et al ., ; Fitza et al ., ; Hajek et al ., ), in particular by two Sirex native to North America, including S. nigricornis (Hajek et al ., ; Olatinwo et al ., ). Although relatively little is understood about the biology and behaviour of S. nigricornis , flexibility in symbiont use could be advantageous now that the competitive S. noctilio is present.…”
Section: Discussionmentioning
confidence: 99%